Hydrosocial cycle and access to water in the periphery of the city of Morelia, Mexico: Case study in La Aldea settlement - García-Estrada, Lorena (2019)
Water is indispensable in the metabolism of cities, but the accelerated peripheral expansion of cities accentuates problems of water access, distribution and quality, which, in turn, are often used by actors with socio-political power that weaken the hydrosocial cycle. The present study analyzed access to water through the hydrosocial cycle in the northern periphery of the city of Morelia, Mexico, specifically in the settelement of La Aldea. The study´s objective was met with field trips, observations, interviews and surveys. Results indicate stress in the hydrosocial cycle wherein there is a dissimilar flow subordinated by political movements and infrastructure development groups. Additionally, population involvement decreased, bottled water and water trucks purchases increased, all while the intervention of the authorities was limited and permissible.